Regulation of hepatic circadian metabolism by the E3 ubiquitin ligase HRD1-controlled CREBH/PPARα transcriptional program - Kim, Hyunbae (Mol Metab, 2021)
OBJECTIVE: The endoplasmic reticulum (ER)-resident E3 ligase HRD1 and its co-activator Sel1L are major components of ER-associated degradation (ERAD) machinery. Here, we investigated the molecular mechanism and functional significance underlying the circadian regulation of HRD1/Sel1L-mediated protein degradation program in hepatic energy metabolism. METHODS: Genetically engineered animal models as well as gain- and loss-of-function studies were employed to address the circadian regulatory mechanism and functional significance. Gene expression, transcriptional activation, protein–protein interaction, and animal metabolic phenotyping analyses were performed to dissect the molecular network and metabolic pathways. RESULTS: Hepatic HRD1 and Sel1L expression exhibits circadian rhythmicity that is controlled by the ER-tethered transcriptional activator CREBH, the nuclear receptor peroxisome proliferator-activated receptor α (PPARα), and the core clock oscillator BMAL1 in mouse livers. HRD1/Sel1L mediates polyubiquitination and degradation of the CREBH protein across the circadian cycle to modulate rhythmic expression of the genes encoding the rate-limiting enzymes or regulators in fatty acid (FA) oxidation, triglyceride (TG) lipolysis, lipophagy, and gluconeogenesis. HRD1 liver-specific knockout (LKO) mice displayed increased expression of the genes involved in lipid and glucose metabolism and impaired circadian profiles of circulating TG, FA, and glucose due to overproduction of CREBH. The circadian metabolic activities of HRD1 LKO mice were inversely correlated with those of CREBH KO mice. Suppressing CREBH overproduction in the livers of HRD1 LKO mice restored the diurnal levels of circulating TG and FA of HRD1 LKO mice. CONCLUSION: Our work revealed a key circadian-regulated molecular network through which the E3 ubiquitin ligase HRD1 and its co-activator Sel1L regulate hepatic circadian metabolism.